VOICES FROM THE MARGINS: A COMPARATIVE STUDY OF SUBALTERNITY IN THE WORKS OF BAMA, SARA ABOOBACKER, AND PRATHIBHA RAY (International Journal of Food and Nutritional Sciences, 2023)
This paper presents a comparative study of subalternity in the works of three prominent Indian authors—Bama, Sara Aboobacker, and Prathibha Ray—whose writings address the intersection of caste, religion, gender, and tribal marginality. Through an exploration of Bama’s Karukku, Aboobacker’s Chandragiriya Theeradalli, and Ray’s Adi Bhumi, the paper examines how these authors amplify the voices of marginalized communities, focusing on women’s experiences of oppression and their resistance against social, religious, and economic structures. Bama, a Dalit Christian writer from Tamil Nadu, highlights the compounded oppression faced by Dalit women, drawing attention to the intersectionality of caste and gender. Her narratives reveal the lived realities of Dalit Christians, critiquing the institutionalized caste system within the church. Sara Aboobacker, a Muslim writer from Karnataka, explores the patriarchal control over Muslim women, addressing religious and societal constraints that limit their autonomy. Her works depict the struggles of Muslim women to navigate and challenge these constraints while seeking personal freedom and empowerment. Prathibha Ray, an Odia writer, brings attention to the plight of tribal women in Odisha, emphasizing the exploitation of both their land and bodies. Through her works, particularly Adi Bhumi, Ray critiques the impact of industrialization, displacement, and patriarchal control on Adivasi communities, offering a poignant portrayal of their resilience. While the authors focus on different cultural, religious, and geographical contexts, their works share common themes of intersectionality, resilience, and resistance. By portraying the agency of marginalized women, they challenge dominant social structures and provide a critical lens through which to understand the complex layers of subalternity in India. This comparative study not only enriches our understanding of subaltern narratives but also highlights the importance of literature in giving voice to those historically silenced by systems of power.